Synergistic antitumor activity of regorafenib and rosuvastatin in colorectal cancer - Yuan, Tao; Wu, Ruilin; Wang, Weihua; Liu, Yue; Kong, Wencheng; Yang, Bo; He, Qiaojun; Zhu, Hong (Frontiers in Pharmacology, 2023)
Colorectal cancer is one of the most prevalent life-threatening malignant tumors with high incidence and mortality. However, the efficacy of current therapeutic regimens is very limited. Regorafenib, a novel multi-kinase inhibitor, has been approved for second- or third-line treatment of patients who are refractory to standard chemotherapy diagnosed with metastatic colorectal cancer, but its clinical efficacy needs to be further improved. Accumulating evidence demonstrates that statins, originally applied as lipid-lowering agents in clinical, also possess potent anticancer activities. However, whether regorafenib and statins pose synergistic anticancer effects in colorectal cancer are still unclear. In our study, we found that regorafenib in combination with rosuvastatin exerted significant synergistic inhibition against colorectal cancer growth in vitro and in vivo. Mechanistically, regorafenib and rosuvastatin combination synergistically suppressed mitogen-activated protein kinases (MAPK) signaling, a crucial signaling pathway promoting cell survival, as indicated by the reduction of phosphorylated MEK/ERK. In addition, regorafenib in combination with rosuvastatin synergistically induced the apoptosis of colorectal cancer in vitro and in vivo. Our study demonstrated the synergistic anti-proliferative and pro-apoptotic effects of regorafenib/rosuvastatin combined treatment in colorectal cancer and provided a novel combination regimen for clinical treatment of colorectal cancer.